2021
DOI: 10.1002/syn.22202
|View full text |Cite
|
Sign up to set email alerts
|

Prelimbic prefrontal cortical encoding of reward predictive cues

Abstract: An environmental cue that predicts the availability of a pleasurable reward can become a powerful incentive unto itself. The process by which this occurs is important to characterize not just because it is essential for normal behavior, but also because it may be involved in impulse control disorders and addiction (Colaizzi et al., 2020;Tomie et al., 2016). One useful model for the study of acquired incentive is conditioned approach (i.e., Pavlovian autoshaping; Brown & Jenkins, 1968), which assesses an animal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 18 publications
1
2
0
Order By: Relevance
“…For example, in female mice, reactivation of a PrL ensemble was most sensitive to identifying ensembles related to persistence in cue reactivity (operant responding) in a single context, while it was most sensitive to persistence of goal‐directed responding (head entries) in different contexts. This is consistent with studies using electrophysiological and calcium imaging methods, which have identified distinct PrL neurons that increase firing in response to a sucrose cue (Grant et al, 2021; Moorman & Aston‐Jones, 2015; Spring et al, 2021). PrL neurons that project to the nucleus accumbens are especially sensitive to sucrose cues (Otis et al, 2017), suggesting that this may be a population tagged in our study.…”
Section: Discussionsupporting
confidence: 88%
“…For example, in female mice, reactivation of a PrL ensemble was most sensitive to identifying ensembles related to persistence in cue reactivity (operant responding) in a single context, while it was most sensitive to persistence of goal‐directed responding (head entries) in different contexts. This is consistent with studies using electrophysiological and calcium imaging methods, which have identified distinct PrL neurons that increase firing in response to a sucrose cue (Grant et al, 2021; Moorman & Aston‐Jones, 2015; Spring et al, 2021). PrL neurons that project to the nucleus accumbens are especially sensitive to sucrose cues (Otis et al, 2017), suggesting that this may be a population tagged in our study.…”
Section: Discussionsupporting
confidence: 88%
“…It is well established that many behavioral functions are specifically regulated by distinct subregions of the PFC. For example, conditioned fear response or trauma (as evidenced in PTSD) is encoded in the ILA 36 , while cue or context-associated reward memory is encoded in PL 37,38 , and compulsive behavior (often associated with drug addiction) is associated with ORBm 39 . Thus, revealing the differential neuron subtype distribution in the different PFC subregions may help link the PFC subregion-specific functions to the various differentially distributed neuron subtypes.…”
Section: Distinct Neuron Subtypes Are Uniquely Enriched In Pfcmentioning
confidence: 99%
“…The rat frontal cortex has been implicated in modulating behavior based on newly computed outcome values. The prelimbic cortex (PrL) neurons show increased responsiveness to cues following cue-outcome associative learning [8][9][10]. In addition, PrL is necessary during learning (i.e., forming associations) to guide subsequent goal-directed behavior [11][12][13][14] following outcome devaluation.…”
Section: Introductionmentioning
confidence: 99%